Hedge funds and the market return - Duarte Cardoso, Daniel; Soares Monte-mor, Danilo; Tardin, Neyla; Neris Nossa, Silvania (Perspectivas Contemporâneas, 2023)
This paper investigates if the equity stake, along with hedge funds, generates value for target companies in highly concentrated markets, such as the Brazilian one. In a sample with 324 Brazilian companies listed in São Paulo Stock Market (B3) that are actively participating in the Anbima Hedge Fund Index (IHFA), between 2007 and 2016, we found that the equity stake of hedge funds generates value in Brazilian invested companies, despite the market being more concentrated. We capture the hedge fund effect on invested companies in terms of: (i) how much the firms’ market capitalization is maintained by hedge funds and its percentage change between t and t-1; (ii) how many funds invest in a determined company each period and its percentage change between t and t-1. We defined target firm value creation using two proxies: abnormal return and effective stock return. To derive our results, we performed linear regressions with funds’ fixed effects and a set of fund characteristics acting as controls. We found a positive and significant relationship between the equity stake of hedge funds and the value generation in invested companies, despite the Brazilian market being more concentrated. Our results suggest that the hedge fund activism is increasing in Brazil, with fund managers influencing firms’ decisions and corporate governance mechanisms.